METHODS AND TECHNOLOGIES OF CREATING PROBLEM SOLVING ACTIVITIES IN TEACHING READING - I. A. Egamberdiyeva (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2024)
Annotation- The study of foreign languages contributes to the general speech development of students. Reading is one of the main types of speech activity. It can act as both a goal and a means of teaching. With the help of reading, a person becomes familiar with the scientific and cultural achievements of mankind, gets acquainted with the art and life of other peoples. The reading process has a huge impact on the formation of personality. With the help of reading, the active and passive vocabulary of words in students is enriched, grammatical skills are formed. Learning to read is one of the problems that received the most complete coverage in the previous stages of the development of the methodology.